Pengaruh Metode Pemberian Tugas Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS Terpadu di SMP Negeri 2 Kabila - Nuralwiyah Sania Sakum; Meyko Panigoro; Sudirman Sudirman; Rosman Ilato; Abdurahim Maruwae (Journal of Economic and Business Education, 2023)
This research employed a quantitative approach. The data were collected through observation, questionnaires, and documentation. The populations in this research were all SMP Negeri 2 Kabila students, totaling 61 students, while the samples were 40 students. The anaysis method employed Simple Linear Regression. The results indicated that the assignment method positively affected student learning outcomes in the Integrated Social Studies subject at SMP Negeri 2 Kabila, Bone Bolango Regency. From the calculation of the coefficient of determination, it indicated an R-square of 0,313, which meant that 31,3% of the variability of student learning outcomes in the Integrated Social Studies subject at SMP Negeri 2 Kabila, Bone Bolango Regency could be explained by the assignment method, while other variables explained the remaining 68,7%.